Advance adsorption assisted data centre cooling in tropics - Mohyong, Clarence Kunjie (Nanyang Technological University, 2022)
Data centres play a fundamental role in supporting the growth and demand for data computing, processing, and cloud storage. In order to maintain the data centre at its working temperature, a significant amount of power is used to cool the temperature of the air and data centre racks. Conventional refrigeration and cooling systems are used to cope with its cooling demands, resulting in adverse environmental impacts. The implementation of adsorption chillers for data centres reduces the impact of cooling methods on the environment as it is more energy efficient and removes the use of refrigerants which causes ozone depletion when exposed.